Grain marketing parastatals in Asia: why do they have to change now? - Rashid, Shahidur; Cummings, Jr., Ralph; Gulati, Ashok (International Food Policy Research Institute, 2005)
Using case studies from six Asian countries, this paper (a) assesses the relevance of underlying rationales for public intervention in foodgrain markets, (b) documents the existing policies and regulations that support operation of grain parastatals, (c) provides estimates of benefits and costs of parastatals, and (d) compares experiences of countries that liberalized (or reduced intervention) with the ones that continue to have significant presence of parastatals. Our results suggest that conditions in the region have improved significantly over the past thirty years; and none of the four commonly agreed rationales—that is, poorly integrated domestic markets, thin and volatile world market, promoting modern technology and the scarcity of foreign exchange reserves—for public intervention in foodgrain markets are now persuasive. Domestic foodgrain markets are integrated, international markets for both wheat and rice are significantly more robust than they were thirty years ago, High-Yielding Varieties (HYV) now cover practically all of the high potential area sown to wheat and rice; and foreign currency reserves have increased dramatically in all countries in recent years. However, although rationales have lost their significance, many countries continue to practice old policies and provide regulatory supports to parastatals, including monopoly control over international trade, preferential access to transportation, restrictions on movement of foodgrains, and cheap or interest-free credit. Relative to the private sector, the costs of the grain parastatals have been high and are increasing, as special interests and rent- seeking are increasingly dictating their operation. This is being manifested in various forms, such as excessive public stocks in India, vacillating import policies in Indonesia and Pakistan, questionable government foodgrain import decisions in the Philippines, and politically-determined ceiling and floor prices in India. On the other hand, the experiences of Bangladesh and Vietnam, both of which have implemented extensive reforms over the last fifteen years, suggest that reduced government intervention can promote competition in the domestic markets, reduce subsidies, and release funds for development and anti-poverty programs without jeopardizing price stability. The paper concludes that reforms are overdue and the delay in changing the old ways of doing price stabilization will be increasingly wasteful.